Prophylactic treatment with PEGylated bovine IFNλ3 effectively bridges the gap in vaccine-induced immunity against FMD in cattle - Attreed, Sarah E.; Silva, Christina; Rodriguez-Calzada, Monica; Mogulothu, Aishwarya; Abbott, Sophia; Azzinaro, Paul; Canning, Peter; Skidmore, Lillian; Nelson, Jay; Knudsen, Nick; Medina, Gisselle N.; de los Santos, Teresa; et al. (Frontiers in Microbiology, 2024)
Foot-and-mouth disease (FMD) is a vesicular disease of cloven-hoofed animals with devastating economic implications. The current FMD vaccine, routinely used in enzootic countries, requires at least 7 days to induce protection. However, FMD vaccination is typically not recommended for use in non-enzootic areas, underscoring the need to develop new fast-acting therapies for FMD control during outbreaks. Interferons (IFNs) are among the immune system's first line of defense against viral infections. Bovine type III IFN delivered by a replication defective adenovirus (Ad) vector has effectively blocked FMD in cattle. However, the limited duration of protection-usually only 1-3 days post-treatment (dpt)-diminishes its utility as a field therapeutic. Here we test whether polyethylene glycosylation (PEGylation) of recombinant bovine IFNλ3 (PEGboIFNλ3) can extend the duration of IFN-induced prevention of FMDV infection in both vaccinated and unvaccinated cattle. We treated groups of heifers with PEGboIFNλ3 alone or in combination with an adenovirus- based FMD O1Manisa vaccine (Adt-O1M) at either 3 or 5 days prior to challenge with homologous wild type FMDV. We found that pre-treatment with PEGboIFNλ3 was highly effective at preventing clinical FMD when administered at either time point, with or without co-administration of Adt-O1M vaccine. PEGboIFNλ3 protein was detectable systemically for >10 days and antiviral activity for 4 days following administration. Furthermore, in combination with Adt-O1M vaccine, we observed a strong induction of FMDV-specific IFNγ+ T cell response, demonstrating its adjuvanticity when coadministered with a vaccine. Our results demonstrate the promise of this modified IFN as a preexposure prophylactic therapy for use in emergency outbreak scenarios.